2009
DOI: 10.1007/s11010-009-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurodegeneration in experimental autoimmune encephalomyelitis (EAE): potential role of inflammation activated myeloperoxidase

Abstract: Experimental Autoimmune Encephalomyelitis (EAE) is a well-established animal model of human multiple sclerosis (MS). The effect of this inflammatory disease on hippocampus has not been addressed. Keeping in view the above consideration an attempt was made to delineate the effect of EAE on the hippocampus of Wistar rats. The assessment of the damage to the hippocampus was done 16 days post induction by the immunolocalization of ChAT (choline acetyl transferase). ChAT decreased remarkably after induction that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…This oligodendrocyte consumption is the explanation of the early neurological onset of MS, characterised by functional disconnection of CNS. Our study, and also studies of other authors, have shown that this lysis can be prevented by the treatment with antagonists of NO production and oxidative species scavengers [15,16,19,25]. These modulators regulated LP intensity regulate the neurological expression of EAE, although it is not a solitary protection mechanism.…”
Section: Suppression Of the Lipid Peroxidation Process In The Cns Redsupporting
confidence: 74%
“…This oligodendrocyte consumption is the explanation of the early neurological onset of MS, characterised by functional disconnection of CNS. Our study, and also studies of other authors, have shown that this lysis can be prevented by the treatment with antagonists of NO production and oxidative species scavengers [15,16,19,25]. These modulators regulated LP intensity regulate the neurological expression of EAE, although it is not a solitary protection mechanism.…”
Section: Suppression Of the Lipid Peroxidation Process In The Cns Redsupporting
confidence: 74%
“…After the experiment, animals were sacrificed and the liver tissues were washed with PBS (pH 7.4) and placed on ice as method described earlier (Sajjad et al, 2009). Briefly, a 50 ml sample was added with 100 ml of Griess reagent and the reaction mixture was incubated for about 5-10 min at room temperature, protected from light.…”
Section: Measurement Of No: Griess Reactionmentioning
confidence: 99%
“…24 Therefore, the possible factors for treating the disease must have the capacity to inhibit the deleterious mechanisms prompted by OS. 25 One of the common models for mimicking OS in vitro involves using H 2 O 2 and the pheochromocytoma (PC)-12 cell line.…”
Section: Introductionmentioning
confidence: 99%